2003
DOI: 10.1002/pits.10077
|View full text |Cite
|
Sign up to set email alerts
|

Social desirability and behavior rating scales: An exploratory study with the Child Behavior Checklist/4–18

Abstract: This study investigated the relationship between the Child Behavior Checklist/4-18 (CBCL/4-18) and two modified measures of social desirability, the Marlowe-Crowne Social Desirability Scale and the Edwards Social Desirability Scale with a sample of 65 parents of normal children from grades K-7. Results from correlational and multiple regression analyses showed that the Aggressive Behaviors and Attention Problems cross-informant syndromes were modestly associated with social desirability scale scores. The relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Parent questionnaires offer only one perspective of the child’s behavior, and ratings may be influenced by other factors such as parental psychological functioning and social desirability (Chilcoat & Breslau, 1997; Merydith, Prout, & Blaha, 2003). In this study cohort at ages fiveand seven, children with PCE were rated by examiners as having more behavioral regulation difficulties during structured testing (Accornero et al, 2006b; Accornero et al, 2005), while parent report on the Achenbach Child Behavior Check List at the same age points found no cocaine-related differences in internalizing or externalizing symptoms (Accornero et al, 2006a; Accornero et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Parent questionnaires offer only one perspective of the child’s behavior, and ratings may be influenced by other factors such as parental psychological functioning and social desirability (Chilcoat & Breslau, 1997; Merydith, Prout, & Blaha, 2003). In this study cohort at ages fiveand seven, children with PCE were rated by examiners as having more behavioral regulation difficulties during structured testing (Accornero et al, 2006b; Accornero et al, 2005), while parent report on the Achenbach Child Behavior Check List at the same age points found no cocaine-related differences in internalizing or externalizing symptoms (Accornero et al, 2006a; Accornero et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In the field of stuttering, there are authors who claim that, despite their importance in the overall process of treatment, parents do not appear to be valid informants [26]. However, studies of behavioural and mental health reveal only slight differences between parents and their children or clinical observers [25,[27][28][29][30]. Some authors [25] point out that parents' responses may be influenced by the desire to please the examiner or to respond as they think is socially acceptable.…”
Section: Introductionmentioning
confidence: 99%
“…The Child Behaviour Checklist (CBCL) is a commonly used instrument worldwide to measure the mental health status of children aged 4-18 years [1,2]. Due to its comprehen-siveness in measurement, it is often used as the gold standard for developing other similar assessment tools.…”
Section: Introductionmentioning
confidence: 99%
“…The English version of CBCL was originally validated in 1989 on a sample of 3000 children, referred and non-referred to mental health services [4]. CBCL and its subscales have been extensively used in research and have shown good validity, reliability, and predictive values [2,4,5,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%